2011
DOI: 10.1186/1742-2094-8-129
|View full text |Cite
|
Sign up to set email alerts
|

Generation of reactive oxygen species in 1-methyl-4-phenylpyridinium (MPP+) treated dopaminergic neurons occurs as an NADPH oxidase-dependent two-wave cascade

Abstract: BackgroundReactive oxygen species (ROS), superoxide and hydrogen peroxide (H2O2), are necessary for appropriate responses to immune challenges. In the brain, excess superoxide production predicts neuronal cell loss, suggesting that Parkinson's disease (PD) with its wholesale death of dopaminergic neurons in substantia nigra pars compacta (nigra) may be a case in point. Although microglial NADPH oxidase-produced superoxide contributes to dopaminergic neuron death in an MPTP mouse model of PD, this is secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
79
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 68 publications
8
79
0
Order By: Relevance
“…Interestingly, we also observed a significant increase in AT1 (and decrease in AT2) receptor expression, which may be related to a feedback mechanism for regulating levels of brain angiotensinogen (O'Callaghan et al, 2011) or to induction of further proinflammatory changes in astrocytes (Clark et al, 2008;Lanz et al, 2010). An increase in AII levels has been shown to increase oxidative stress in neurons (Joglar et al, 2009;Zawada et al, 2011) and to enhance the microglial neuroinflammatory response (Rodriguez-Pallares et al, 2008;Villar-Cheda et al, 2012). Furthermore, in the present study, we observed that estrogen, via ER-a, also induces direct neuroprotection of dopaminergic neurons; thus, in cultures of the dopaminergic neuron cell line (i.e., in the absence of glia), the ER-a agonist PPT inhibits the loss of dopaminergic cells induced by MPP þ and MPP þ þ AII, possibly by inhibition of neuronal oxidative stress and apoptosis (Brendel et al, 2013;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Interestingly, we also observed a significant increase in AT1 (and decrease in AT2) receptor expression, which may be related to a feedback mechanism for regulating levels of brain angiotensinogen (O'Callaghan et al, 2011) or to induction of further proinflammatory changes in astrocytes (Clark et al, 2008;Lanz et al, 2010). An increase in AII levels has been shown to increase oxidative stress in neurons (Joglar et al, 2009;Zawada et al, 2011) and to enhance the microglial neuroinflammatory response (Rodriguez-Pallares et al, 2008;Villar-Cheda et al, 2012). Furthermore, in the present study, we observed that estrogen, via ER-a, also induces direct neuroprotection of dopaminergic neurons; thus, in cultures of the dopaminergic neuron cell line (i.e., in the absence of glia), the ER-a agonist PPT inhibits the loss of dopaminergic cells induced by MPP þ and MPP þ þ AII, possibly by inhibition of neuronal oxidative stress and apoptosis (Brendel et al, 2013;Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 67%
“…In animal models of PD, hyperactivation of the local RAS exacerbates the inflammatory microglial response, oxidative stress and dopaminergic degeneration, all of which are inhibited by angiotensin receptor blockers (for reviews, see Labandeira-Garcia et al, 2013;Wright and Harding, 2012). Recent studies have shown that AII-induced activation of the NADPHoxidase complex (Joglar et al, 2009;Rodriguez-Pallares et al, 2008;Zawada et al, 2011) and activation of the microglial RhoA/Rho kinase pathway are involved in AII-induced oxidative stress and neuroinflammation. In the present study, we observed that RAS inhibition plays a major role in the beneficial effects of estrogen, which was confirmed by the neuroprotective effect of RAS inhibition by candesartan after LTED (i.e., when the ERT is unable to decrease RAS activity).…”
Section: Discussionmentioning
confidence: 98%
“…In neurotoxin-induced parkinsonism with 6-OHDA and MPTP the role of RAS has been studied and evidences indicate that in these models up-regulated levels of AII, exacerbates the DAergic neuronal death mediated by AT1Rs [86]. Experimental data also support the involvement of brain RAS in dopaminergic degeneration [110,111,112]. It was demonstrated that AII increased the neurotoxic effect induced by low doses of 6-OHDA, and the treatment with inhibitors of ACE [113,114,112] or blockage of AT1Rs [98,95,96] resulted in a significant reduction of both the loss of dopaminergic neurons and the levels of protein oxidation and lipid peroxidation induced by the neurotoxins [115].…”
Section: Renin-angiotensin Systemmentioning
confidence: 70%
“…Various isoforms of NADPH have been identified in neurons and glial cells of the CNS 11, 14, 65, 68, 93 and previous clinical and animal studies have shown their importance for pathogenesis of injury following ischemia 48, 53 . Compared with slices from wild type mice in control conditions, slices from R+A+ animals had similar expression levels of Nox2, but elevated expression levels of Nox4.…”
Section: Discussionmentioning
confidence: 99%